Market Overreaction pada Bursa Efek Indonesia dengan Size Effect Sebagai Variabel Pemoderasi - Tanady, Melisa; Sukamulja, Sukmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to examine market overreaction phenomenon and market overreaction impact on abnormal return that moderated by size effect of LQ45 index between five years period (2015-2019). Secondary data on Indonesian Stock Exchange website are taken as samples.   Wilcoxon test and interaction effects regression test are used to prove the evidences. The Wilcoxon test is developed in order to confirm that market overreaction occurs on winner and loser portfolio. The result shows that market overreaction occurs in the short and long term. Interaction effects regression test shows the size effect as moderating variable does not strengthen or weaken the relationship of market overreaction to abnormal returns. The findings show that company size has an independent effect, which means abnormal returns are more common in large companies. Size effect concept does not occur in the Indonesia Stock Exchange, especially the firms that always in the LQ45 index during the period of research.